Sound And Celebration of Death: Gong Ensembles in The Secondary Mortuary Rituals of the Jarai (Central Vietnam) Compared with Those of the Dayak Benuaq (East Kalimantan, Indonesia). Do They Originate from the Dong Son Culture? - Della Rata (Graduate School of Institut Seni Indonesia Yogyakarta, 2016)
The Jarai people are an Austronesian language speaking group living in Central Vietnam. They reached mainland Southeast Asia from Northern Borneo, or possibly from the Malay Peninsula, around the 5th century B.C. as part of the more general migratory movement that took the Austronesian people from Formosa to Madagascar, westwards, and to Easter Island, eastwards. The Pa thi ritual is one of the most remarkable of the many ceremonies celebrated by the Jarai, in terms of its magnificence and the complexity of the elements involved. Pa thi (the “tomb abandonment”) is a secondary mortuary ritual that allows the spirits of the dead to reach their final destination. When the ritual is held, the tomb, carefully decorated with symbolic elements, becomes the centre of a sumptuous feast, lasting three days, which includes gong music, dances and buffalo sacrifices. The aim of this paper is to analyse some features of the Pa thi ceremony and to compare them with some of the scenes depicted on the Dong Son bronze drums (Heger I type). In fact, as many scholars such as Goloubew (1929) and Bemet Kempers (1988) have pointed out, there is a connection between the people of Dong Son and “men who might be the more direct ancestors of the Indonesians we know from the archipelago”. As evidence of this connection, these scholars explicitly mentioned the culture of the Dayak people of Borneo and the mountain populations living in Central Vietnam. In addition to my analysis of the Jarai ritual, I will give a few comments on the Kwangkai, the secondary mortuary ritual of the Dayak Benuaq people (East Kalimantan, Indonesia). Rather than attempting to provide a definite analysis of the bronze drums, this paper intends to open some new perspectives for a better understanding of the scenes depicted on the bronze drums as well as giving an interpretation based on the comparison with living rituals.